Risk Based Inspection Analysis of a Vacuum Distilation Unit of a Refinery/MSc Mechanical Engineering and Design - Karali Angela; Pefanis Themistoklis (2018)
Acknowledgements, Abstract, Acronyms, Introduction, Risk Based Inspection, Overview of RBI Methology, Corrosion Rate and Remaining Life Determination, RBI Software, Vacuum Distilation Unit (VDU), General Arrangement, Process Description, Main Equipment, RBI to the VDU, Data Collection and Review, Equipment Analysis, Results and Discussion, References, Appendices.